Antioxidant activity of papaya extract during wound healing is enhanced by Se2+ addition - Nafiu, Bidemi Abdulrazaq; Rahman, Mohammad Tariqur (2014)
The healing efficiency of cutaneous wound increases when Se2+ is added to the unripe papaya phosphate buffered saline (PBS) extract. This study investigated protection against oxidative damage in cutaneous wound by using Se2+ or Zn2+ added unripe papaya PBS extract; Induced cutaneous wound on rat were topically treated twice/day with 20 μL of extract dissolved in deionised water (5 mg/mL) where Se2+ and Zn2+ was separately added at 0.1 μg/mg extract and 100 μM concentrations respectively. Control groups were treated with deionised water (negative) and solcoseryl (positive). The excised wound homogenate at day 4 and 10 post wounding was used to analyse antioxidants enzyme activities (catalase, superoxide dismutase, glutathione peroxidase) and lipid peroxidation. Se2+ added extract significantly (p< 0.05) reduced the wound size as compared to negative and positive controls throughout the observation period and on days 1 and 7 respectively. Positive control and the extract significantly (p< 0.05) reduced wound size on days 1-5 and 7-9 respectively. Se2+ added extract significantly (p< 0.05) increased the enzymes’ activities on day 4 and 10 compared to negative control and day 4 only when compared to positive control. Remaining treatments significantly (p< 0.05) increased activity of catalase on day 4 and 10 and superoxide dismutase on day 4 only when compared to negative control. All treatments significantly (p< 0.05) decreased lipid peroxidation at day 4 and 10 post wounding. Thus, Se2+ added papaya extracts provide increased protection against oxidative damage during wound repair.